Senyawa Penyusun Hasil Fraksi Etil Asetat Minuman Sinom Campuran Jeruk Nipis Dan Madu (curcuma domestica val-tamarindus indica l.) - Ni Ketut Wiradnyani; Dhylla Hanggaeni Dyah Puspaningrum (Master Program of Food Science and Technology, Faculty of Agricultural Technology, Udayana University, 2018)
Sinom beverage mixture of lime and honey alternative functional food. The ingredients are curcumin and young tamarin leaves as a sinom beverages mixture lime juice and honey, it is easily available, relatively in cheap that is consumed, it contains antioxidant compounds. This study aimed to identification constituen compound result of ethyl acetate fraction of sinom beverage mixture of lime and honey in vitro. With GCMS analysis of method. Ethylacetate fraction all egedly contain compounds : 1-butanamine, N-methyl-N-nitro(0,56%), L-Sorbose (5,96%), 3-Furaldehyde ( 0,32%), Propylcarbamate (2,95%), 2,4 Dihydroxy-2,5-dimethy1 -3(2H)-furan-3-one (1,20 %), 4H-Pyran-4-one, 3-hydroxy-2-methy1(%), 4,5-Diamino-2-hydroxpyrimidine (2,75%), Propanal, 2,3-dihydroxy-,(S)- (3,88%), 4H-Pyran-4-one,2,3-dihydro-3,5-dihydroxyl-6-methyl-(5,04%), -Hydroxymethylfurfural (7,76 %), 3-Buten-2-one,4-(2-azido-1-hydroxy-2,6,6-trimethylcyclohexyl) butanoic acid, 3 oxo-,hexyl ester (3,28 %), N,N’- Dimethyl-1,4-butanediamine (1,05%), Epicurzerenone (0,81%), Cyclotrisiloxane, hexamethyl (4,03%),,42,1- furan, dodecahydro-6,9a-dimethyl-, 3aS-(3a.alpha.,5a.alpha.,6.alpha.,9a.beta.,9b.alpha.) (17,90%), -(4-Hydroxyphenyl) -4-methyl-2-pentanone (27,31%), Tumerone (2,62%), Arsenous acid,tris (trimethylsily1) ester(5,58%). The result showed 18 constituen compound result of ethylasetat fraction of sinom beverage mixture of lime and honey. The mayor antioxidant compounds are 4H-Pyran-4-one,2,3-dihydro-3,5-dihydroxyl-6-methyl-(5,04%) and 2,4 Dihydroxy-2,5-dimethy1 -3(2H)-furan-3-one (1,20 %).